EXECUTION OF MORTGAGE RIGHTS THROUGH AUCTION IMPLEMENTATION WITHOUT COURT DECISION (STUDY OF SUPREME COURT DECISION NUMBER 3600 K/PDT/2020) - Dona, Rahma; Setyono, Yoni Agus (International Journal of Social Service and Research, 2024)
The Law on Dependent Rights provides convenience and certainty for Holders of Dependent Rights to carry out execution through public auctions. The execution of the right of dependency can be carried out in two ways, namely the Execution Parate based on Article 6 of the Law on the Rights of Dependency, or through the Fiat  of the District Court Execution based on Article 14 paragraphs (2) and (3) of the Law on the Rights of Dependency. In this writing, the main focus is to analyze the lawsuit against the defendant who is considered an unlawful act in the execution of the right of dependency through the implementation of an auction. This paper is expected to provide a comprehensive overview of the legal consequences arising from the existence of a civil lawsuit against the auction of the execution of the Right of Dependency and whether it is possible to conduct an auction without a court determination. The research used the doctrinal research method with the type of research used by the author based on its nature as an explanatory research, using case data in the Supreme Court Decision Number 3600 K/Pdt/2020 associated with principles, legal norms and laws and regulations. Lawsuits and fights create legal uncertainty for the Holder of Dependent Rights, auction buyers and other parties related to the execution of Dependent Rights.